2018
DOI: 10.1155/2018/9828070
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Trauma Changes the Parvalbumin-Positive Neurons in Rat Auditory Cortex

Abstract: Acoustic trauma is being reported to damage the auditory periphery and central system, and the compromised cortical inhibition is involved in auditory disorders, such as hyperacusis and tinnitus. Parvalbumin-containing neurons (PV neurons), a subset of GABAergic neurons, greatly shape and synchronize neural network activities. However, the change of PV neurons following acoustic trauma remains to be elucidated. The present study investigated how auditory cortical PV neurons change following unilateral 1 hour n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
(38 reference statements)
1
6
1
Order By: Relevance
“…There are three main findings in the present study. First, contrary to previous reports of increased and unaltered PV neuron density, we found significantly reduced PV neuron density and PV expression in AI 5 and 10 d after loud noise exposure (Nguyen et al, 2017;Liu et al, 2018). In the case of Nguyen et al (2017), the researchers used a bilateral noise exposure paradigm with a free field speaker at a lower volume of 102-104 dB SPL which could account for our different results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There are three main findings in the present study. First, contrary to previous reports of increased and unaltered PV neuron density, we found significantly reduced PV neuron density and PV expression in AI 5 and 10 d after loud noise exposure (Nguyen et al, 2017;Liu et al, 2018). In the case of Nguyen et al (2017), the researchers used a bilateral noise exposure paradigm with a free field speaker at a lower volume of 102-104 dB SPL which could account for our different results.…”
Section: Discussioncontrasting
confidence: 99%
“…In the case of Nguyen et al (2017), the researchers used a bilateral noise exposure paradigm with a free field speaker at a lower volume of 102-104 dB SPL which could account for our different results. In the case of Liu et al (2018), although more similar to our paradigm, the hearing lesion was conducted at a higher frequency of 16 kHz (in rats, which have a lower hearing range), and only for 1 h rather than two. Our result is consistent with findings that NIHL reduced cortical inhibitory synaptic transmission and PV neuron function after noise exposure (Qiu et al, 2000;Seki and Eggermont, 2003;Kotak et al, 2005;Eggermont, 2006;Sun et al, 2008;Yang et al, 2011;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For tinnitus and likely other trauma-related brain diseases, an initial reduction in GABAergic transmission occurs prior to symptom onset 38 . In noise exposure-induced tinnitus, reduced IPSCs in AI excitatory neurons, GABAergic and glycinergic neurotransmission in inhibitory neurons, as well as PV-neuron density, have been reported [39][40][41][42][43][44] . Whether this reduced density is caused by loss of PV-neurons or reduced PV expression is still an open question that needs further experimentation.…”
Section: Enhanced Inhibition On Evoked and Spontaneous Activities M-mentioning
confidence: 97%
“…Previous studies reported changes in PNNs in the primary auditory cortex following auditory deprivation [6,7]. Noise-induced hearing loss in postnatal 4-weekold mice reduced PNNs, and this change was initiated as early as 1 day after noise exposure [6].…”
Section: Introductionmentioning
confidence: 92%